Sustaining Customary Forest Governance in Indonesia: A Systematic Literature Review of Legal Recognition and Functional Authority in Riau Province - Eno Suwarno; Muhammad Rawa El Amady; Nurul Qomar; Emi Roslinda (Green Insight Solutions, 2026)
Despite global recognition of their crucial role, indigenous institutions in Riau Province, Indonesia, face intense pressure from agribusiness expansion, revealing a critical gap between constitutional recognition and functional authority in customary forest governance. This study aims to analyze the structural and functional roles of customary institutions in Riau’s forest management and identify challenges and opportunities for their integration into national policy. Using a systematic qualitative literature review and content analysis, it synthesizes evidence from literature (2000-2025). The research findings are quite striking: Customary institutions in Riau play a very significant strategic role. They regulate ecological-spiritual zoning, enforce laws based on customary norms, and resolve conflicts restoratively. These functions are clearly essential elements for sustainable forest management. However, the gap remains. On the one hand, recognition of land ownership rights is indeed growing. However, the formal integration of customary institutions into state institutions remains very limited. The results of this study concluded that the goal of community-based forest management must go beyond mere recognition of land rights. It needs to encourage the emergence of hybrid governance. To achieve equitable and sustainable forest management—both in Riau Province, Indonesia and in the global context—bridging the gap between legal recognition and truly effective customary institutional authority is essential.